Angled Insertion of Microneedles for Targeted Antigen Delivery to the Epidermis - Rohan Murty; Abishek Sankaranarayanan; Isabella I. Bowland; Juan Mena-Lapaix; Mark R. Prausnitz (MDPI AG, 2022)
Peanut and tree nut allergies account for most food-induced anaphylactic events. The standard allergy immunotherapy approach involves subcutaneous injection, which is challenging because severe adverse reactions can occur when antigens spread systemically. Allergen localization within the epidermis (i.e., the upper 20-100 µm of skin) should significantly reduce systemic uptake, because the epidermis is avascular. Microneedle (MN) patches provide a convenient method for drug delivery to the skin, but they generally target both epidermis and dermis, leading to systemic delivery. In this study, we adapted MN technology for epidermal localization by performing angled insertion of 250 µm-long MNs that limits MN insertion depth mostly to the epidermis. We designed a biplanar insertion device to aid the repeatability of angled insertions into porcine skin ex vivo at specified angles (90°, 45°, and 20°). When compared to 90° insertions, MN application at 20° decreased mean insertion depth from 265 ± 45 µm to 97 ± 15 µm. Image analysis of histological skin sections revealed that acute-angle insertion increased epidermal localization of delivery for antigen-coated MNs from 25% ± 13% to 70% ± 21%. We conclude that angled insertion of MNs can target antigen delivery to epidermis.